2018
DOI: 10.1016/j.cemconres.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray nanotomographic and spectromicroscopic study of the tricalcium aluminate hydration in the presence of gypsum

Abstract: The rheology of modern Portland cement (PC) concrete critically depends on the correct dosage of gypsum (calcium sulfate hydrate) to control the hydration of the most reactive phase-tricalcium aluminate (C 3 A). The underlying physio-chemical mechanism, however, remains unsolved mainly due to the lack of high-spatialresolved and chemistry-sensitive characterization of the C 3 A dissolution frontier. Here, we fill this gap by integrating synchrotron-radiation based crystallographic, photon-energy-dependent spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…They found that, as soon as being in contact with sulfur-containing solution, C 3 A would undergo rapid dissolution owing to the quick growth of ettringite as well as the formation of AFm phases (but quickly vanish), and then followed by slow dissolution of C 3 A, which might probably be due to ion-complexation. 35 Similar observation was found in the case of C 3 A-gypsum system suggesting both the nucleation and growth of the s-AFm phases as the rate controlling mechanism. 15…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…They found that, as soon as being in contact with sulfur-containing solution, C 3 A would undergo rapid dissolution owing to the quick growth of ettringite as well as the formation of AFm phases (but quickly vanish), and then followed by slow dissolution of C 3 A, which might probably be due to ion-complexation. 35 Similar observation was found in the case of C 3 A-gypsum system suggesting both the nucleation and growth of the s-AFm phases as the rate controlling mechanism. 15…”
Section: Resultssupporting
confidence: 73%
“…Meantime, the deposited ettringite would react with C 3 A at the contact surface, as shown in eqn (10), to form calcium-aluminate-monosulfate (s-AFm). Geng et al 35 applied nanotomographic and spectromicroscopic techniques to evaluate the C 3 A hydration in the presence of gypsum (CaSO 4 ). They found that, as soon as being in contact with sulfur-containing solution, C 3 A would undergo rapid dissolution owing to the quick growth of ettringite as well as the formation of AFm phases (but quickly vanish), and then followed by slow dissolution of C 3 A, which might probably be due to ion-complexation.…”
Section: Resultsmentioning
confidence: 99%
“…Though, there is still no consensus on which chemical species or surface complex is responsible for passivation of the C 3 A surface. Some studies have argued that the passivation layer comprises of SO 2− 4 ions 12,34 ; although, results contradicting this argument have been presented in a study conducted by Collepardi et al 41 Other studies [37][38][39] , have reported that Ca-Al-SO 3 complexes, that preferentially adsorb onto the Alrich C 3 A surface, are responsible for passivating it.…”
Section: Stage Imentioning
confidence: 99%
“…Notably, X‐ray synchrotron analysis and other examinations of C 3 A particulates' surfaces have shown that a metastable calcium aluminate hydrate phase does form on C 3 A surface; however, this phase does not appear to inhibit dissolution of C 3 A or the transport of ions from C 3 A surface to the contiguous solution. In other studies, a surface passivation mechanism has been theorized to be at the origin of retardation of C 3 A hydration during the period when ettringite crystals grow at a slow rate. Though, there is still no consensus on which chemical species or surface complex is responsible for passivation of the C 3 A surface.…”
Section: Review Of Hydration Of C3a In [C3a + C$ + H] Pastesmentioning
confidence: 99%
See 1 more Smart Citation